Time of Onset of Necrotizing Enterocolitis and Focal Perforation in Preterm Infants: Impact on Clinical, Surgical, and Histological Features - Janet Elizabeth Berrington; Janet Elizabeth Berrington; Nicholas David Embleton; Nicholas David Embleton (Frontiers Media S.A., 2021)
Objective: There is no gold standard test for diagnosis of necrotizing enterocolitis (NEC). Timing of onset is used in some definitions and studies in an attempt to separate NEC from focal intestinal perforation (FIP) with 14 days used as a cutoff. In a large, detailed data set we aimed to compare NEC and FIP in preterm infants born <32 weeks gestation, presenting before 14 days of life in comparison to cases presenting later.Design: Infants with NEC or FIP when parents had consented to enrollment in an observational and sample collection study were included from 2009 to 2019. Clinical, surgical, histological, and outcome data were extracted and reviewed by each author independently.Patients/Episodes: In 785 infants, 174 episodes of NEC or FIP were identified of which 73 (42%) occurred before 14 days, including 54 laparotomies and 19 episodes of medically managed NEC ("early"). There were 56 laparotomies and 45 episodes of medically managed NEC presenting on or after 14 days age ("late").Results: In early cases, 41% of laparotomies were for NEC (22 cases) and 59% for FIP (32 cases), and in late cases, 91% of laparotomies (51 cases) were for NEC and 9% (five cases) were for FIP. NEC presenting early was more likely to present with an initial septic presentation rather than discrete abdominal pathology and less likely to have clear pneumatosis. Early cases did not otherwise differ clinically, surgically, or histologically or in outcomes compared with later cases. FIP features did not differ by age at presentation.Conclusions: Although most FIP occurred early, 14% occurred later, whereas almost one third (29%) of NEC cases (surgical and medical) presented early. Infant demographics and surgical and histological findings of early- and late-presenting disease did not differ, suggesting that early and late cases are not necessarily different subtypes of the same disease although a common pathway of different pathogenesis cannot be excluded. Timing of onset does not accurately distinguish NEC from FIP, and caution should be exercised in including timing of onset in diagnostic criteria.